SAT0713 Survey on prevalence of rheumatic disorders in bangladeshi adults. (15th June 2017) - Ahmed, S; Haq, SA; Al-qadir, AZ; Rahman, MM; Paul, S
Abstract : Background: From Community based COPCORD (community oriented program for control of rheumatic diseases) study in Bangladesh about a quarter of people is suffering from musculoskeletal disorders. But the study was conducted over a small number of samples and some specific localities of the country. So further study was required, covering the whole Bangladesh to justify this high prevalence. Objectives: To determine the prevalence of musculoskeletal symptoms and specific rheumatic disorders in adult population of Bangladesh. Methods: In this survey, a total of 2000 individuals aged 18 years or older were selected in twenty clusters (primary sample unit) from the seven divisions of the country. Modified COPCORD (Community Oriented Program for Control of Rheumatic Disorders) questionnaire was used to detect positive respondents. Standard criteria were used for diagnosing rheumatic disorders. Clinical judgment was used to solve diagnostic problems. Results: In total 1843 individuals were interviewed with a response rate of 92.1%. The point prevalence of musculoskeletal pain was 33.7%. It was higher in women (38.7%) than men (28.4%) and higher in rural (34.5%) than that in urban (32.4%) areas. Higher prevalence rates were observed in homemakers (16.0%), laborers (3.0%), business professionals (2.9%) and cultivators (2.8%). Low back (23.3%), knee (12.7%) and shoulder (6.1%) were the most frequent site of complaint. Non specific low back pain (12.7%) and knee osteoarthritis (7.3%) were the two top ranking disorders. The prevalence of rheumatoid arthritis was 1.6% and spondyloarthritis 1.2%. 5.5% of the respondents had disability from rheumatic problems. Conclusions: About one third of the Bangladeshi adults suffer from musculoskeletal pain at a given point of time. There are residence and gender variation in the prevalence rates. Low back and knee pain were the principal sites of complaints. Disclosure of Interest: None declared